Choice preferences in drum tower design among the Dong people: Evidence from the five villages in Guangxi, China - Siyi Jia; Wanyu Guo; Mohd Hafizal Bin Mohd Isa; Zalena Binti Abdul Aziz; Muhamad Azhar bin Ghazali (Frontiers of Architectural Research)
Chengyang Eight Village is renowned as a gathering site for the Dong ethnic group and the most prominent area for wooden architecture. Drum tower is an extremely important representative of wooden architecture that can influence the economic and tourism development of the region, providing functions of public activities, communication, and ethnic identity. However, widespread issues such as damage, abandonment, or disappearance threaten drum towers, which are crucial spiritual centres for Dong villages. Despite the social and functional significance of drum towers, there is a lack of comprehensive understanding of how people interact with them. This study aims to analyse Dong people's choice preferences in drum tower design, to examine the importance of 84 practices and influencing factors and propose a research path for study choice preferences. This study selected five villages among the Chengyang Eight Village as the research sites. Based on data from literature, field investigations, questionnaires and statistical analysis methods, this study analysed the choice preferences of local villagers regarding drum tower design. Five steps, 24 elements and 84 practices of drum towers were studied, and the impacts of the four influencing factors (Practicality, Economy, Decoration, and Belonging) on the three levels of the 84 practices were examined. Results showed that drum towers are a part of a complex, mutually reinforcing system where villagers and the towers mutually promote and influence each other. Villagers exhibited ambivalence towards drum tower design, navigating between deep-rooted traditions and evolving functional needs in contemporary contexts. Drawing on the Space-Behaviour Interaction Theory, this study examined the interaction between villagers and drum towers through a comprehensive approach of qualitative and quantitative methods, and established a research path for choice preferences. This study significantly enriches the discourse on minority village studies and traditional architecture, and provides valuable references for cultural heritage preservation and policy formulation.